Birds at Laurie Island, South Orkney Islands, Antarctica: Breeding species and their distribution - Coria, Néstor Rubén (2011)
Bird communities of the ice-free areas of Laurie Island were surveyed during the breeding seasons of 1993/94 and 1994/95. Additional censuses of penguin colonies were made during the 2004/05 season. Twenty-nine seabird species were recorded, of which 15 were breeding. Adélie Penguins Pygoscelis adeliae bred at six localities, primarily on the south coast. This survey showed that the population of Adélie Penguins in the 2004/05 season was 32.3% lower than that found a previous study conducted during the 1983/84 season. Chinstrap Penguins Pygoscelis antarctica are the most numerous pygoscelid penguins in the area. Previous studies showed they had increased between 1948 and 1983 at many colonies. Since then, there was a slight increase in the population between 1983/84 and 1994/95 (from 141 950 to 143 792 breeding pairs, +1.3%). However, populations of Chinstrap Penguins in the Antarctic Peninsula showed different trends in the late 1980s. Because the censuses available from Laurie Island after 1994/95 season were incomplete, it is not possible to draw any conclusions about Chinstrap Penguin population trends. Population size and distribution of several other species breeding in the area are updated, and possible factors affecting short-term changes are discussed.